2022
DOI: 10.1021/acs.jafc.2c00530
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Taste Characteristics of Kokumi N-Lactoyl Phenylalanine in the Presence of Phenylalanine and Lactate

Abstract: N-l-Lactoyl phenylalanine (N-l-lactoyl-Phe) has been identified as a taste-active contributor in many fermented foods. However, its preparation, taste property, and content in foodstuffs are little known to date. In the current study, two preparation technologies of N-l-lactoyl-Phe including heating and enzymatic methods were investigated. Other investigations include its taste property and quantification in several fermented foods. The results indicated that the heating preparation and enzymatic preparation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…As shown in Table , the N - l -Lac- l -Trp solution after pH adjustment exhibited a kokumi-like taste with a recognized threshold of 100 mg/L, an astringent taste with a recognized threshold of 200 mg/L, and a bitter taste with a recognized threshold of 400 mg/L. In our previous study, the N - l -Lac- l -Phe aqueous solution also has a complex taste at a similar recognized threshold . As far as we can gather from the previous literature, the taste properties of N - l -lactoyl amino acid derivatives were dependent on amino acids at the N-terminus.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…As shown in Table , the N - l -Lac- l -Trp solution after pH adjustment exhibited a kokumi-like taste with a recognized threshold of 100 mg/L, an astringent taste with a recognized threshold of 200 mg/L, and a bitter taste with a recognized threshold of 400 mg/L. In our previous study, the N - l -Lac- l -Phe aqueous solution also has a complex taste at a similar recognized threshold . As far as we can gather from the previous literature, the taste properties of N - l -lactoyl amino acid derivatives were dependent on amino acids at the N-terminus.…”
Section: Resultsmentioning
confidence: 83%
“…It was evident that N - l -Lac- l -Trp, N - l -Lac- l -Phe, and N - l -Lac- l -Tyr were the most promising stimulators for taste receptors. Previously, we found that N - l -Lac-Phe was a kokumi compound with an intrinsic complex taste in water . Accordingly, N - l -Lac- l -Trp and N - l -Lac- l -Tyr caught our attention for further taste evaluation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations